A modification to the WAVE breakup model for evaporating diesel spray. (5th September 2016) - Gao, Haobu; Li, Xiangrong; Xue, Jiye; Bai, Honglin; He, Xu; Liu, Fushui
Highlights: The effect of environmental and injection parameters on the WAVE C2 is discussed. The relationship between the WAVE C2 and background temperature is demonstrated. A variable C2 WAVE model based on temperature is used to simulate an engine test. Abstract: In order to improve the accuracy of the WAVE breakup model for an evaporating spray, it was calibrated using a series of diesel spray experiments with different orifice diameters, injection pressures, background gas densities and temperatures. The calibration focused on liquid length and spray (vapor) penetration. Based on the calibration results, it is concluded that the standard WAVE model with a constant C2, which is an adjustment parameter for breakup time, accurately predicts liquid length and spray penetration with a variety of orifice diameters, injection pressures and background gas densities. However, the same cannot be said for background temperature. Background temperature strongly affects the C2 value. Particularly, the C2 decreases with an increase in background temperature. Interestingly, the relationship between the C2 value and the background temperature seems to be of approximate inverse proportion. Therefore, due to this relationship between the C2 value and background temperature, and in order to obtain greater simulation accuracy, the proposed WAVE model with a variable C2 was developed and used to simulate a single-cylinder diesel engine. It was found that there is a significant decrease in liquid length alongside the development of the in-cylinder spray and combustion process. This is reasonable because liquid droplets break-up and evaporate faster in a higher temperature environment. Moreover, the result is in accordance with images from optical diesel engine experiments captured and performed by others.